An Age-Related Hearing Protection Locus on Chromosome 16 of BXD Strain Mice - Qing Yin Zheng; Lihong Kui; Fuyi Xu; Tihua Zheng; Bo Li; Melinda McCarty; Zehua Sun; Aizheng Zhang; Luying Liu; Athena Starlard-Davenport; Ruben Stepanyan; Bo Hua Hu; et al. (Neural Plasticity)
Inbred mouse models are widely used to study age-related hearing loss (AHL). Many genes associated with AHL have been mapped in a variety of strains. However, little is known about gene variants that have the converse function—protective genes that confer strong resistance to hearing loss. Previously, we reported that C57BL/6J (B6) and DBA/2J (D2) strains share a common hearing loss allele in Cdh23. The cadherin 23 (Cdh23) gene is a key contributor to early-onset hearing loss in humans. In this study, we tested hearing across a large family of 54 BXD strains generated from B6 to D2 crosses. Five of 54 strains maintain the normal threshold (20 dB SPL) even at 2 years old—an age at which both parental strains are essentially deaf. Further analyses revealed an age-related hearing protection (ahp) locus on chromosome 16 (Chr 16) at 57~76 Mb with a maximum LOD of 5.7. A small number of BXD strains at 2 years with good hearing correspond roughly to the percentage of humans who have good hearing at 90 years old. Further studies to define candidate genes in the ahp locus and related molecular mechanisms involved in age-related resilience or resistance to AHL are warranted.